Influência do padrão alimentar e de acasalamento em parâmetros reprodutivos de Triatoma williami Galvão, Souza & Lima, 1965 (Hemiptera-Reduviidae) - Câmara, Thaís Peres (2016)
Chagas disease is caused by Trypanosoma cruzi protozoonosis that can cause sudden death in chronic adult by involvement of the nervous system, heart and digestive. Species of wild triatomine with synanthropic potential has been incriminated as potential vectors of T. cruzi. Adult specimens of Triatoma williami, native of the Brazilian Midwest, has been found in anthropogenic environments and naturally infected with T. cruzi in the municipality of Barra do Garças - MT. However, we have not yet found colonies of these insects in human habitations. The potential to colonize an environment associated with the reproductive success of a species. In addition, proceeds from the food has a direct effect on reproductive females. Thus, the objective of this study was to investigate the pattern of mating and feeding influence on reproductive parameters of females of T. williami. The insect fifth instar were individualized and after adult females were divided into two groups mated and isolated. Exposure to food source was held fortnightly in mice and heavy females before and after each meal. Matings were defined by the number of found spermatophore, and oviposition was observed for 30 days and the number of outbreaks. Our results showed that fertility and fecundity were higher in feed and manting while the lifetime was similar between the two groups. Feed and manting females requiring less blood meal to produce an egg, and the number of matings was positively related to fertility of female maturation.